2007
DOI: 10.4319/lo.2007.52.3.1079
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12 and iron colimitation of phytoplankton growth in the Ross Sea

Abstract: Primary production in the Ross Sea, one of the most productive areas in the Southern Ocean, has previously been shown to be seasonally limited by iron. In two of three bottle incubation experiments conducted in the austral summer, significantly higher chlorophyll a (Chl a) concentrations were measured upon the addition of iron and B 12 , relative to iron additions alone. Initial bacterial abundances were significantly lower in the two experiments that showed phytoplankton stimulation upon addition of B 12 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
259
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(276 citation statements)
references
References 54 publications
16
259
1
Order By: Relevance
“…Our field results show that because large areas in the ocean do not contain sufficient B vitamins, the efficiency of the biological pump may be controlled not only by the availability of mineral nutrients, such as Fe, N, and P, but by vitamin accessibility. Although recent field studies have confirmed the ecological importance of B 12 , because phytoplankton growth was enhanced by picomolar B 12 amendments in both coastal and open ocean environments (12,14,15,19,20), no field study has yet addressed the relevance of the other B vitamins measured in the present study. Because some bacterial groups seem to be major producers of the organic cofactors required by eukaryotic phytoplankton, B vitamins illustrate the complexity of the prokaryote/eukaryote codependency via ectocrine relationships in the marine environment.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Our field results show that because large areas in the ocean do not contain sufficient B vitamins, the efficiency of the biological pump may be controlled not only by the availability of mineral nutrients, such as Fe, N, and P, but by vitamin accessibility. Although recent field studies have confirmed the ecological importance of B 12 , because phytoplankton growth was enhanced by picomolar B 12 amendments in both coastal and open ocean environments (12,14,15,19,20), no field study has yet addressed the relevance of the other B vitamins measured in the present study. Because some bacterial groups seem to be major producers of the organic cofactors required by eukaryotic phytoplankton, B vitamins illustrate the complexity of the prokaryote/eukaryote codependency via ectocrine relationships in the marine environment.…”
Section: Resultsmentioning
confidence: 75%
“…The seasonal distributions of vitamins indicate that their concentrations vary from undetectable to a few picomoles per liter (11,12). However, those studies were mostly limited to vitamin B 12 (9)(10)(11)(12)(13)(14)(15)(16), and it is unclear whether or not those results can be extended to other essential B vitamins. The limited information that exists suggests that this is not the case (16)(17)(18)(19)(20).…”
mentioning
confidence: 98%
“…light at depth or iron in high-nutrient, lowchlorophyll-HNLC-regions). Lately, recognition of simultaneous stresses has popularized discussions on 'co-limitation' (Price & Morel 1991;Morel et al 1994;Bertrand et al 2007;Saito et al 2008). In a sense though, phytoplankton growth is always concurrently constrained by every essential environmental resource that requires energy and/or reductant to acquire or concentrate.…”
Section: The Integrated Growth Environment and Optimizationmentioning
confidence: 99%
“…Direct measurements of B-vitamin concentrations in coastal ocean systems found picomolar concentrations and complex patterns in the distributions of several vitamins, including thiamin (Sañ udo-Wilhelmy et al, 2012; Barada et al, 2013). In bottle experiments, iron and B-vitamins, particularly vitamin B 12 , acted synergistically to increase phytoplankton and bacterial productivity, suggesting colimitation (Panzeca et al, 2006;Bertrand et al, 2007). Supporting the view that the exchange of vitamins between species is important, adaptive strategies for coping with low vitamin concentrations have been identified in diatoms .…”
Section: Introductionmentioning
confidence: 99%